Risk of bloodstream infection in patients with renal dysfunction: a population-based cohort study - Dagasso, Gabrielle (Epidemiol Infect, 2020)
Although patients with end-stage renal disease (ESRD) are known to be at high risk for developing bloodstream infections (BSI), the risk associated with lesser degrees of renal dysfunction is not well defined. We sought to determine the risk for acquiring and dying from community-onset BSIs among patients with renal dysfunction. A retrospective, population-based cohort study was conducted among adult residents without ESRD in the western interior of British Columbia. Estimated glomerular filtration rates (eGFR) were determined for cases and incidence rate ratios (IRR) were calculated using prevalence estimates. Overall, 1553 episodes of community-onset BSI were included of which 39%, 32%, 17%, 9%, 2% and 1% had preceding eGFRs of ≥90, 60–89, 45–59, 30–44, 15–29 and <15 ml/min/m(2), respectively. As compared to those with eGFR ≥60 ml/min/m(2), patients with eGFR 30–59 ml/min/m(2) (IRR 4.4; 95% confidence interval (CI) 3.9–4.9) and eGFR <30 ml/min/m(2) (IRR 7.0; 95% CI 5.0–9.5) were at significantly increased risk for the development of community-onset BSI. An eGFR <30 ml/min/m(2) was an independent risk factor for death (odds ratio 2.3; 95% CI 1.01–5.15). Patients with renal dysfunction are at increased risk for developing and dying from community-onset BSI that is related to the degree of dysfunction.